(untitled) (Plant Tissue Culture and Biotechnology, 2018)
An experiment was carried out to optimize the doses and combinations of growth regulators for in vitro propagation of Dendrobium Red Bull through shoot tip culture. The experiment was laid out according to completely randomized design with 15 treatments and three replications. For multiple shoot induction, newly grown shoot buds (keikies) were cultured on MS supplemented with various combinations of NAA and BAP. The regenerated plants were transferred to ex vitro in different substrates and acclimatized. Best response for the shoot length (21.19 mm) was obtained from the medium supplemented with 3.0 mg/l BAP with 1.5 mg/l NAA. Similarly maximum number of leaves was observed from the same combination at all the recorded days except 60 days, whereas the maximum shoot number (7.66) was obtained from the medium containing 3.0 mg/l BAP + 1.0 mg/l NAA. The shoots were then transferred to root inducing medium and well rooted plants were transferred to different substrates. Survivability of the regenerated plants varied from 60 to 92%. The substrate containing cocodust showed maximum survivability (92%) whereas minimum (60%) was observed from the substrate containing course sand. BAP and NAA proved to be good growth regulators for in vitro multiplication of Dendrobium. Plant Tissue Cult. & Biotech. 28(2): 161-169, 2018 (December)